From Presence to Performance: An Empirical Study of College English Online Learning Through the CoI Lens - Yu Liu (International Journal of Education and Humanities, 2026)
The rapid advancement of information technology and the widespread adoption of online education have intensified the need to improve the quality of College English e-learning. Despite the growing prevalence of digital instruction, challenges remain in maintaining students’ engagement and achieving effective learning outcomes. To address this issue, the present study aims to examine how different aspects of teaching presence influence student engagement and, subsequently, learning performance in an online College English environment. Guided by the Community of Inquiry (CoI) framework, this research develops and validates a structural model that links teaching presence → student engagement → learning performance. Using data collected from a College English massive open online course (MOOC), the study employs partial least squares structural equation modeling (PLS-SEM) to test the hypothesized relationships among the variables. The results reveal that among the three dimensions of teaching presence—design and organization, facilitating discourse, and direct instruction—only facilitating discourse significantly enhances behavioral, emotional, and cognitive engagement. Furthermore, student engagement serves as a key predictor of learning performance, with cognitive engagement demonstrating the strongest effect, followed by emotional and behavioral engagement. These findings emphasize that fostering interactive and dialogue-rich learning environments is crucial for improving students’ engagement and performance in online College English learning. Theoretically, this study extends the CoI framework to second-language acquisition by identifying the differential effects of teaching presence. Practically, it highlights the importance of instructors adopting the role of facilitators who cultivate meaningful online learning communities that promote both quality and equity in digital education